Intention to use mobile payment services in India: an empirical analysis. (11th April 2022) - Choudhury, Nayanjyoti; Mahanta, Monoshree
Mobile payments are becoming increasingly common in our lives today. With the COVID-19 pandemic, people have been pushed to use mobile payment services as it is a far more resilient form of payment compared to cards and cash due to its contactless feature. Nonetheless, research in this area still remains nascent in the Indian context and this paper aims to test a conceptual model in order to determine the factors affecting adoption of mobile payment systems. Data was collected from 650 respondents from the metros and tier 1 and tier 2 cities in India. Results from the structural equation modelling revealed personal innovativeness, perceived ease of use and perceived usefulness positively influence attitude, and attitude has a positive impact on intention to use mobile payment services. The findings also suggest a strong impact of personal innovativeness on perceived ease of use. The paper offers practical implications and directions for future research.